PENGARUH KECUKUPAN MODAL DAN RISIKO KREDIT TERHADAP PROFITABILITAS: LIKUIDITAS SEBAGAI PEMEDIASI Pada Bank Perkreditan Rakyat di Kabupaten Badung - Agustini, Ni Luh Putu Budi; Wiagustini, Ni Luh Putu; Purbawangsa, Ida Bagus Anom (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.06.TAHUN 2017, 2017)
ABSTRACT The purpose of this study is to examine and analyze (1) the effect of capital adequacy to liquidity, (2) the effect of credit risk to liquidity, (3) the effect of capital adequacy on profitability, (4) the effect of credit risk on profitability, (5) the effect of liquidity to profitability, (6) liquidity role in mediating the effects of capital adequacy on profitability, (7) liquidity role in mediating the effect of credit risk on profitability. This study used 52 Bank Perkreditan Rakyat in Badung R egency period 2013-2015. The data used in this study is secondary data from the Financial Statements of Bank Perkreditan Rakyat in Badung R egency, published by Bank Indonesia. The data were analyszed by Path Analysis with SPSS program. The results of the study found that (1) the capital adequacy significantly have positive effect on liquidity, (2) credit risk significantly have negative effect on liquidity, (3) the capital adequacy significantly have positive effect on profitability, (4) credit risk significantly have negative effect on profitability, (5 ) liquidity significantly have positive effect on profitability, (6) liquidity have a partial mediation effect of capital adequacy on profitability, (7) liquidity have a partial mediation effect of credit risk on profitability.
Keywords: Capital Adequacy, Credit Risk, Liquidity, Profitability